THE EFFECT OF LEARNING MOTIVATION AND SELF EFFICACY ON PROBLEM SOLVING ABILITY ON STUDENTS FACULTY OF ECONOMICS AND BUSINESS UNESA - Ramadhani Ayunia; Novi Marlena (Institute of Computer Science (IOCS), 2022)
This study aims to analyze and examine the effect of learning motivation and selfefficacy on problem-solving abilities in students of the Faculty of Economics and Business, Unesa. The respondents of this study were 100 active students of the Faculty of Economics and Business Unesa class 2018-2021. The data collection technique was through a questionnaire, then the data analysis technique used was multiple regression. The results of this study showed that learning motivation had a partial effect on problem-solving abilities, self-efficacy partially affected problemsolving abilities and learning motivation and self-efficacy together had an effect on problem-solving abilities. Based on the results of this study, researchers provide suggestions for students to be able to increase intrinsic and extrinsic motivation. For lecturers, it is hoped that they can help their students to increase learning motivation and self-efficacy. For further researchers, it is recommended to be able to develop variations of other variables that can affect problem solving abilities during online learning.